Stroke with Subarachnoid Hemorrhage: Assessment of Cerebrovascular Pressure Regulation and Simulated Cerebrovascular Resistance - Daley, Michael L. (2008)
Monitoring methods designed to assess cerebrovascular regulation and increased cerebrovascular resistance (CVR) of patients with subarachnoid hemorrhage (SAH) would facilitate therapeutic intervention and potentially reduce secondary complications. The aim of this study was to assess changes of cerebrovascular regulation and CVR by evaluating changes of cerebrovascular pressure transmission in patients with SAH. Admission Hunt-Hess grades, Fisher scores, Glasgow Outcome Scores (GOS) at 6 months, and pressure recordings were obtained from 20 patients. Biomechanical models of cerebrovascular pressure transmission were constructed over one-minute intervals for the initial and final two hours of post-hemorrhage monitoring. Classified according to the GOS score at 6 months, eight patients died (GOS 1), five were severely disabled (GOS 3), and seven patients were moderately disabled (GOS 4). During the initial monitoring period 100%, 80%, and 28.6% of groups with GOS 1, 3, and 4 demonstrated impairment of cerebrovascular regulation; whereas, in the final monitoring period 100%, 100%, and 14.3% respectively demonstrated impairment. Between monitoring periods, simulated CVR (sCVR) significantly increased (p < 0.001) for patients with GOS 1 and 3 and decreased for those with GOS 4 with mean resistance for the latter group significantly lower (p > 0.001) than other means. Loss of cerebrovascular regulation and increased sCVR were observed in SAH patients with poor outcome.